Collaboration : individuals working together - Davis, Jennifer; Daniels, Ryn (O'Reilly, 2018)
A large part of what makes a DevOps initiative successful is getting people to work together more effectively than they did previously. In this lesson, you'll learn how to build communicative relationships, shared goals and empathy for a more effective, collaborative work culture.